APPLYING THE FORMS AND METHODS OF ORGANIZING TECHNOLOGY LESSONS IN THE CONDUCT OF PRACTICAL TRAINING (American Journal of Interdisciplinary Research and Development, 2026)
This article investigates the application of the forms and methods of organizing technology lessons in the conduct of practical training from a research-based methodological perspective. The study argues that modern technology education should not be limited to the transmission of technical information or the reproduction of manual operations; it must function as a competence-oriented pedagogical system that develops technological thinking, design culture, problem-solving capacity, safety awareness, cooperative behavior, professional orientation and creative performance. The article analyzes the didactic potential of frontal, individual, pair, group, brigade, laboratory-practical, workshop-based, project-based and digitally supported forms of lessons. It also examines explanatory, demonstrative, problem-based, project-based, case-based, instruction-card, technological-map, collaborative, criterion-referenced and reflective methods as instruments for increasing the effectiveness of practical training. As a result, an integrated methodological model is proposed for organizing practical technology lessons through diagnostic-preparatory, motivational-problem, instructional-design, practical-executive, monitoring-corrective and presentation-reflective stages. The model emphasizes that practical training becomes educationally meaningful only when goal, content, form, method, tool, safety requirement, assessment criterion and reflection are connected into one coherent pedagogical process.